2005
DOI: 10.1093/ajcn/81.5.1133
|View full text |Cite
|
Sign up to set email alerts
|

A controlled 2-mo dietary fat reduction and soy food supplementation study in postmenopausal women

Abstract: Background: Low intake of dietary fat and high intake of soy foods have been suggested to partly explain the lower breast cancer rates in Asia, perhaps because of lower endogenous estrogens. Objective: The objective was to assess the hormonal and nonhormonal effects of diets resembling an Asian diet in terms of total fat and soy food contents. Design: Fifty-seven postmenopausal women participated in a randomized, controlled, dietary intervention study. The subjects consumed a very-low-fat diet (VLFD; 11% of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Although one observational study found that higher soy intake was associated with lower serum levels of estrogens, 29 randomized trials in general did not observe any effect. 30,31 However, a 30 g soy milk powder supplement increased SHBG concentrations in a 10-week trial. 32 Soy intake is a component of the AHEI, however, the 1990 FFQ only assessed soy bean or tofu intake and may underestimated intake of soy from soy milk and foods containing soy protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although one observational study found that higher soy intake was associated with lower serum levels of estrogens, 29 randomized trials in general did not observe any effect. 30,31 However, a 30 g soy milk powder supplement increased SHBG concentrations in a 10-week trial. 32 Soy intake is a component of the AHEI, however, the 1990 FFQ only assessed soy bean or tofu intake and may underestimated intake of soy from soy milk and foods containing soy protein.…”
Section: Discussionmentioning
confidence: 99%
“…Human intervention and cross-sectional studies that have investigated the effect of phytoestrogens or soy intake on hormone levels in postmenopausal women have been small and produced inconsistent results (4,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). This study is the largest study ever conducted to investigate the relationship between phytoestrogen exposure and circulating sex hormone levels in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…There is suggestion in some cross-sectional studies that circulating oestrogen and androgen levels may be nonsignificantly decreased in association with high-soy food intake but these effects are typically small and the results are not consistent. Results from the nearly 20 shortterm intervention studies on soy (mainly given as supplements or other soy protein products) and circulating oestrogen and sexhormone-binding globulin are mixed and this may be related to differences in study design, small sample sizes, the amount and source of soy isoflavones that were used, duration of supplementation and other reasons (for a review, see Maskarinec et al, 2004;Wu et al, 2005). Fewer studies have investigated the effect of soy intake on mammographic density.…”
Section: Soy and Markers Of Breast Cancer Riskmentioning
confidence: 99%